2006
DOI: 10.1111/j.1442-2018.2006.00254.x
|View full text |Cite
|
Sign up to set email alerts
|

Iranian staff nurses’ views of their productivity and management factors improving and impeding it: a qualitative study

Abstract: As the biggest proportion of hospital personnel, Iranian nurses have a major role in providing quality care to patients. Nursing managers and nurses no longer feel that nurses' work is valued and they are concerned about their productivity. Nurses' views about productivity and management factors affecting it have been identified as the most important aspects affecting productivity. Thus, this study assesses productivity from the nurse's view. A grounded theory approach was used for this research. Purposive sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
35
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 14 publications
7
35
2
Order By: Relevance
“…The consequences can be dissatisfaction, lack of motivation, and low quality of service among nurses, all of which leading to patient dissatisfaction (42,43). Our results support the results of previous studies and confirm the poor psychosocial environment among nurses.…”
Section: Discussionsupporting
confidence: 83%
“…The consequences can be dissatisfaction, lack of motivation, and low quality of service among nurses, all of which leading to patient dissatisfaction (42,43). Our results support the results of previous studies and confirm the poor psychosocial environment among nurses.…”
Section: Discussionsupporting
confidence: 83%
“…Most studies have reported the PA of nurses at low levels (13,20,27,43), and the results of these studies are in the same direction as this study. Several studies have indicated opposite results, with most nurses at low (28, 43) levels in EE and at low (28,43) to medium (21) levels in DP, which are not in line with the results of the present study.…”
Section: Discussioncontrasting
confidence: 56%
“…In Iran, the productivity of nurses, which consists of the majority of health care staff, has been one of the major issues for health system managers in recent years and in this regard, they have appealed to the government to take certain actions such as privatization (28). Numerous researches have also reviewed nurses' burnout levels (17,27,(29)(30)(31)(32)(33)(34)(35)(36).…”
Section: Introductionmentioning
confidence: 99%
“…This shows that clinical service section is understaffed [22,23]. Lack of enough human force has been reported by many studies as one of the common problems from the nurses' viewpoint [24,25]. Apparently, managers need to reevaluate safety culture of hospital and focus more on preventive programs.…”
Section: Discussionmentioning
confidence: 99%